Sugiharti Halim (2008): A Cinematic Portrayal of Chinese Indonesian's Ambiguous Identity (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2021)
Sugiharti Halim (2008) provides a cinematic insight into the lives of Chinese Indonesians whose identities are perpetually labeled as liyan (other) in the eyes of the inlanders (pribumi). It narrates the story of Sugiharti Halim, a Chinese Indonesian girl, who struggles with her Indonesian sounding name which, instead of successfully assimilating her Chinese identity, makes her even more Chinese than before. This study aims to investigate the cinematic portrayal of Chinese Indonesian’s ambiguous identity as experienced by the female protagonist. The writer employs close textual analysis of the indie film and approaches the issue by the reading of cinematic codes (mise en scene) and the theoretical perspective of name giving developed by Watzlawik in 2016. The conflict highlited in this “indie” criticizes the position of Chinese filmmaker for being pigeoholed on the ground of their ethnicity as portrayed in most commercial films which put Chinese more as a marginalized group. Therefore, the study reveals that films have become a new means of politicizing the interest of certain ethnic group which somehow puts the Chinese Indonesians in their most vulnerable position. The study also concludes that independent films help the young Chinese filmmakers to reconnect with their Chinese heritage as they begin to pick up bits of their Chineseness which were previously miscontrued by the inherited ideals of the New Order regime.